2015
DOI: 10.17224/energagric.2015v30n4p338-343
|View full text |Cite
|
Sign up to set email alerts
|

Construction Material Interference on Air Temperature and Humidity Inside the Piglet Creep Area

Abstract: Piglet development in the farrowing house is a determining factor for the economic success of the farm, being essential to use means to ensure the survival and the satisfactory performance of the piglets in this phase. The objective was to evaluate the thermal comfort of two different creeps for piglets. For this, it was used a farrowing house with four individual pens, two made of wood, and two of polyethylene. Inside each creep and at the geometric center of each room, a data logger was installed to record t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Most of the researches with different heating systems for pigs (McGINNIS et al, 1981;SILVA et al, 2005, SABINO et al, 2015 have shown significant results in the use of heated floors due to the heat transfer by conduction from the floor to the animals, being a more thermally efficient method.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the researches with different heating systems for pigs (McGINNIS et al, 1981;SILVA et al, 2005, SABINO et al, 2015 have shown significant results in the use of heated floors due to the heat transfer by conduction from the floor to the animals, being a more thermally efficient method.…”
Section: Resultsmentioning
confidence: 99%